Sociological ambivalence in three Latin American corporate control institutions: Revisoría Fiscal - Colombia (Fiscal Audit), Comisaría - Mexico (Statutory Examiner) and Sindicatura - Argentina (Statutory Audit) - Ramírez Henao, Driver Ferney; González González, Patricia (Cuadernos de Administración, 2020)
The Revisoría Fiscal (Fiscal Audit), Comisaría (Statutory Examiner), and Sindicatura (Statutory Auditor) are institutions that exercise corporate oversight in order to preserve the general interest. In order to achieve their objective, these institutions must keep private and public interests balanced. However, upholding these interests impartially can lead to contradictions because of the tensions each interest group generates. Thus, from the theoretical framework of sociological ambivalence, this paper understands the type of contradictions arising in the corporate control that the aforementioned institutions exercise. To account for the types of ambivalence, firstly, we identify the contradictions that have been recorded in academic papers, and then, based on oral accounts, these contradictions are analyzed. In both cases, qualitative content analysis is applied. It is concluded that the control figures studied present sociological ambivalence since they are linked to 1) contradictory structural demands, 2) conflict of status and 3) conflicting purposes.